Modified SPWM technique for single phase variable voltage nine level inverter for PV system - Venkateswarlu, Meesala; Sateesh, Gopisetti; Sujatha, Peddakotla (Institute of Advanced Engineering and Science, 2023)
Multilevel inverters are widely popular because they boost the overall staging of the network with low harmonic distortion, less strain, and simply create highest possible development in industrial and electrical vehicle applications. Here a hybrid multilevel inverter having few switches compare to traditional multi-level inverters has been implemented. It has the capability to operate as a 3-level, 5-level, 7-level and 9-level inverter with different magnitudes of output voltage by varying the modulation index without changing of circuit topology and switching sequences. A new variable amplitude phase opposition disposition sinusoidal pulse width modulation (VAPODPWM) technique is proposed to control the inverter. In this concept unsymmetrical carrier wave form, i.e. A single triangular wave is divided into three triangular waves of different magnitude was chosen. it reduces the volt-sec of output due to that it gives less total harmonic distortion (THD) compare to other conventional space pulse width modulation (SPWM) techniques and conventional space vector pulse width modulation (CSVPWM) control techniques. The ease of conversion capability with less count of switches and operation with less THD shows the effectiveness of the converter. The converter is simulated by using MATLAB/Simulink and results are discussed.